(untitled) (Communication & Society, 2012)
The Information society is bringing about an increase in the number of information referents for deaf signers (those who use sign language). With the aim of exploring the ways most commonly used by deaf people to find out about current affairs, this paper summarizes some quantitative research that was carried out involving 138 deaf people: 69 in Spain and 69 in the US. The work is complemented qualitatively by a focus group in Gallaudet University, Washington, using American Sign Language (ASL), and by observations from three lecture/ news presentations which took place in Barcelona in Catalan Sign Language (LSC).